Pengaruh Kualitas Pelayanan, Harga Dan Promosi Terhadap Keputusan Pembelian Tiket Pada Aplikasi Access By Kai Di PT. Kereta Api Indonesia (Persero) Daop 9 Jember Stasiun Probolinggo - Sari, Lusi Novita; Tumini, Tumini; Dhany, Umi Rahma (Universitas Panca Marga, 2024)
Purchasing decisions in determining or choosing the type of product to buy are certainly not something that just happens in a relatively short time. Before consumers decide to buy a product, consumers will also consider several things that can influence purchasing decisions, for example service quality, price, promotions, and so on. This research aims to determine the quality of service, prices and promotions on ticket purchasing decisions on the Access By KAI application at PT. Kereta Api Indonesia (Persero) Daop 9 Jember Probolinggo Station in February 2024 is the population of the study. The sampling technique used in this research is nonprobability sampling in the form of purposive sampling. Data collection uses documentation and questionnaires. Data analysis uses quantitative analysis with validity test, reliability test, classic assumption test (normality test, multicollinearity test and heteroscedasticity test), multiple linear analysis test, coefficient of determination (R2), t test (partial) and dominant test using the IBM SPSS application v.23.0. The results of testing service quality, price and promotion partially have a significant positive effect on purchasing decisions.